Reforming Suburbia : The Planned Communities of Irvine, Columbia, and The Woodlands - Forsyth, Ann, 1963- (Book collections on Project MUSE., 2005)
The ""new community"" movement of the 1960s and 1970s attempted a grand experiment in housing. It inspired the construction of innovative communities that were designed to counter suburbia's cultural conformity, social isolation, ugliness, and environmental problems. This richly documented book examines the results of those experiments in three of the most successful new communities: Irvine Ranch in Southern California, Columbia in Maryland, and The Woodlands in the suburbs of Houston, Texas. Based on new research and interviews with developers, designers, and residents, Ann Forsyt.